New neoplastic agents - Moura , Thamires Chagas; Lira, Emanuel Batista de Sousa; Santos , Leonardo Junio dos; Santos, Daniel Henrique Santiago Leon dos (Seven Editora, 2024)
New neoplastic agents represent a significant advance in oncology, offering innovative therapeutic options for the treatment of various neoplasms. These agents include targeted therapies, immunotherapies, and precision medicine approaches that specifically target cancer cells while minimizing damage to normal tissues. Targeted therapies focus on inhibiting specific molecular pathways involved in cancer growth and progression, such as tyrosine kinase inhibitors and monoclonal antibodies. Immunotherapies harness the power of the immune system to recognize and attack cancer cells, including immune checkpoint inhibitors and chimeric antigen receptor T cell (CAR-T) therapy. Precision medicine approaches involve the use of genomic profiling and molecular biomarkers to tailor treatment strategies to individual patients, allowing for more personalized and effective therapies. Overall, the new neoplastic agents offer promise of improved outcomes and quality of life for cancer patients, marking a paradigm shift in the management of this complex disease. DOI:https://doi.org/10.56238/sevened2024.012-004